Hydroponic home-based vegetable production system manual - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
This manual on hydroponics provides, in very simple language, step-by-step instructions for the cultivation of a variaty of crops. The IICA, Office in Guyana, is pleased to provide producers with this alternative methods of cultivation to assist in food security, improvement of household nutrition and also provide a means of improving incomes